Indonesian perspectives on managing the Asean haze - Varkkey, Helena (Faculty of Arts and Social Sciences, University of Malaya, 2009)
This article examines Indonesia’s reactions towards regional haze management efforts between October 2006 and September 2007. Two significant developments occurred during this time, drawing attention to Indonesia’s sovereignty sensitivities. Firstly, while Indonesia at first seemed to be moving towards ratification of the ASEAN Agreement on Transboundary Haze Pollution, it abruptly decided to set up a special committee to study the treaty, effectively halting the parliamentary ratification process. Secondly, aft er asking for regional help by inviting ASEAN member countries to assist areas of their choosing, Indonesia later refused to approve their proposals. The article argues that Indonesia is reluctant to give up control over its sovereignty due to the shadow of a bloody colonial history, bitter foreign interventionist experiences, territorial disputes with its neighbours, and ongoing internal conflicts. External non-intervention is especially important to Indonesia now, in the process of decentralizing and dealingwith the arising internal complications, especially those involving forest resources. The paper concludes that these developments could be part of a bigger attempt by Indonesia to regain its past glory as the de facto leader of ASEAN, enabling it to use its influence to strengthen the non-interference principle to protect its sovereignty during the delicate decentralization process.